Republic of Congo : Staff Report-Press Release; Staff Report; Debt Sustainability Analysis, and Statement by the Executive Director for the Republic of Congo. (IMF Staff Country Reports; Country Report, 2019)
The Republic of Congo was hit hard by the oil price shock and delayed fiscal adjustment, amidst governance challenges and unsustainable debt. While program negotiations were long and complex, the authorities made decisive progress in 2018 and early 2019 with decisive fiscal consolidation, and the implementation of a large package of structural reforms, including two rounds of prior actions to improve governance and transparency. In addition, financing assurances have been secured.